6th conference annuelle de l’ACSI/6th Annual CAIS Conference: Mieux communiquer l’information: une nouvelle etape/To better communicate information: a new step - Canadian Association for Information Science (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
See PDF